2019
DOI: 10.1002/jcb.29356
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA (MEG3) in urinal exosomes functions as a biomarker for the diagnosis of Hunner‐type interstitial cystitis (HIC)

Abstract: Background Toll‐like receptor‐7 (TLR7) is functionally involved in the pathogenesis of Hunner‐type interstitial cystitis (HIC). In addition, maternally expressed gene 3 (MEG3) is implicated in many urethral diseases. In this study, we aimed to verify the hypothesis that exosomal MEG3 in urine can be used as a novel diagnostic biomarker for HIC. Methods Electron microscopy was utilized to observe the distribution of urinary exosomes between the case group and the control group. Receiver operating characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The up-regulated DEGs were mainly enriched in the extracellular region, extracellular space, and external side of the plasma membrane, while the down-regulated DEGs were mainly enriched in the extracellular exosome, apical plasma membrane, and bicellular tight junction. Some studies have suggested that the long noncoding RNA MEG3 in urine exosomes can be used as a biomarker for IC/ BPS (16). Stellavato et al (17) suggested that continuous loss of extracellular matrix may be related to inflammation in IC/BPS.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulated DEGs were mainly enriched in the extracellular region, extracellular space, and external side of the plasma membrane, while the down-regulated DEGs were mainly enriched in the extracellular exosome, apical plasma membrane, and bicellular tight junction. Some studies have suggested that the long noncoding RNA MEG3 in urine exosomes can be used as a biomarker for IC/ BPS (16). Stellavato et al (17) suggested that continuous loss of extracellular matrix may be related to inflammation in IC/BPS.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal MEG3: From the PubMed screening, we found no studies on MEG3 associated with lung diseases and exosomes. However, three recent studies could describe exosomal MEG3 in high-grade serous carcinoma [163], cervical cancer [164], and Hunner-type interstitial cystitis [165]. These studies underline that MEG3 may be involved in intercellular communication, especially in cancers, and therefore further research on this topic is needed to assess its relevance in lung diseases.…”
Section: Meg3 and Lung Cancermentioning
confidence: 99%
“…First, these lncRNAs may trigger important hallmarks of cancers, such as "Genome instability and mutation" for CDKN2B-AS1 [87,121], "Activating invasion and metastasis" for FENDRR [196], "Resisting cell death" for MEG3 and CDKN2B-AS1 [118,154,157,160,207], and "Sustaining and proliferative signaling" for TUG1 [83]. Secondly, previous studies in other cancers found an exosomal expression of MEG3, TUG1, and CDKN2B-AS1 [163][164][165]201,202,215]. These findings suggest that MEG3, TUG1, and CDKN2B-AS1 may also be involved in lung cancer intercellular communication.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Accumulative evidence has indicated that the relative abundance of these molecule-bearing urinary exosomes is altered in various kidney diseases [7]. In fact, it has been proposed that several exosome-derived molecules, such as aquaporins (AQPs) [8], miR-125a and miR-351 [6], RNA (MEG3) [9], RNA HOTAIR [4], and fetuin-A, could have potential application as biomarkers [10].…”
Section: Introductionmentioning
confidence: 99%